CHARACTERISTICS OF THINKING IN STUDENTS PSYCHOLOGICAL BASIS OF THE LEARNING PROCESS (Academia Science Repository, 2023)
Speech is a tool of thinking. When a certain idea is expressed in words, the process of thinking is carried out. Expressing an idea in words is a complex process that consists of stages such as the motive of expression (speech goal), internal speech, and external speech expression of an idea. Thinking is the movement of ideas that reveal the essence of things. Its result is not an image, but a certain idea. Thinking is a theoretical and practical activity of a special type, which assumes a system of actions and procedures that have a directional-exploratory, re-changing and cognitive nature. In this article, thoughts and opinions about what thinking is, its types, characteristics and stages of development are discussed.